Effects of tidal barrier on estuarine hydrodynamics and sedimentation - Huynh Ngoc Trien; Suphat Vongvisessomjai; Tawatchai Tingsangchali; Preecha Kamronrithisorn; Government of New Zealand (Bangkok : Asian Institute of Technology, 1987)
Tidal barrier is a very common structure in estuarine areas. It serves as a barrier against the salinity intrusion or high tide to avoid flooding. When the tidal barrier is constructed there are some other effects besides the main purposes. In the present study, the hydrodynamic effect is considered with 3 different cases of barrier operation: fully closed, fully open and partly open. The analytical solution developed by Prof. Suphat Vongvisessomjai and Somchai Rojakamthorn is used for fully open case; a reduction factor of tidal amplitude at the barrier is found for partly open case then the former solution can be used again with the modified tidal amplitude. For the fully closed case the Chezy's equation is used to describe the velocity field. Subsequently, the sedimentation effect of the tidal barrier is considered. From the mass transport equation, a first order of Galapatti's asymptotic solution is used with some simplifications. For the steady, unsteady uniform cases, analytical solutions in closed forms are obtained; for the general unsteady slowly varying flow a simplified governing equation is derived and from this equation, simple numerical calculation can be proceeded. The results of velocity field are good; for the sediment part, the computed results agree very well with experimental results ( for sinusoidal velocity field ) and can fairly describe the sediment distribution for the unsteady flow in the Savannah estuary. Then both hydrodynamics and sedimentation models are applied to the Chao Phraya estuary. For the 4 cases of 1962, the results showed that both models could be applied for a rough estimation. It is also estimated t hat the barrier will cause some deposition in the river due to the decrease of turbulence when t he barrier is fully closed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Hydrodynamics; Estuarine sediments